Pandemic Vibrio parahaemolyticus O3:K6 on the American continent - Velazquez-Roman, Jorge; León-Sicairos, Nidia; Hernandez-Diaz, Lucio D.; Canizalez-Roman, Adrian (Frontiers in Cellular and Infection Microbiology, 2014)
Vibrio parahaemolyticus is one of the most important seafood-borne bacterial in recent years and is the leading causal agent of human acute gastroenteritis, primarily following the consumption of raw, undercooked or mishandled marine products. Until 1996, infections caused by V. parahaemolyticus were generally associated with diverse serovars. However, in February 1996, a unique serovar (O3:K6) of V. parahaemolyticus with specific genetic markers (tdh, toxRS/New and/or orf8) appeared abruptly in Kolkata, India. In subsequent years, O3:K6 isolates similar to those isolated in Kolkata have been reported from food borne outbreaks in Southeast Asia, as well as in the Atlantic and Gulf coasts of the United States (U.S). More recently, there have been reports in Europe, Africa and Central and South America. Specifically, in the American continent, some countries have reported cases of gastroenteritis due to the pandemic O3:K6 strain and its serovariants; the pandemic strain was first detected in Peru (1996, >100 cases), subsequently spreading to Chile in 1998 (>16,804 human cases), to the U.S. in 1998 (>700 cases), to Brazil in 2001 (>18 cases) and to Mexico in 2004 (>1200 cases). The arrival of the pandemic clone on the American continent may have resulted in a significant shift on the epidemic dynamics of V. parahaemolyticus. However, although O3:K6 is the predominant serovar of the recognized clinical strains in some countries in the Americas, a decrease in clinical cases caused by O3:K6 and an increase in cases associated with a new serotype (O3:K59, Chile) have been recently reported. The emergence and worldwide dissemination of O3:K6 and other pandemic strains since 1996 have come to represent a threat to public health and should concern health authorities. This review focuses on the presence, distribution and virulence factors of the V. parahaemolyticus O3:K6 pandemic clone and its serovariants in clinical and environmental strains on the American continent.